Principles of addiction medicine : the essentials - Cavacuiti, Chris; American Society of Addiction Medicine (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkin s, 2009)
"Principles of Addiction Medicine: The Essentials is a compact and p ortable distillation of the American Society of Addiction Medicine's fl agship text, Principles of Addiction Medicine. This handbook present th e clinically essential points from the larger text in an easy-to-follow outlined and bulleted format. Each chapter follows a template with str uctured headings such as pharmacokinetics, pharmacodynamics, therapeuti c uses, effects, liability, and withdrawal. Principles of Addiction Med icine: The Essentials is an excellent reference for a wide variety of a ddiction medicine professionals, including psychiatrists, psychologists , psychiatric nurses, social workers, internal medicine/primary care ph ysicians, and substance abuse counselors"--Provided by publisher.
Keywords: Substance abuse; Substance-Related Disorders -- therapy -- Handbooks; Behavior, Addictive -- Handbooks; Substance-Related Disorders -- diagnosis -- Handbooks